The Nexus Between Green Finance, Green Energy, Green Technology, and Fintech: A Pathway to Sustainable Development - Topaloglu, Emre Esat; Nur, Tuğba; Ege, Ilhan (My University, 2025)
Green finance, energy, technology, and fintech are essential drivers of a sustainable environment and the promotion of sustainable development. This study analyzes the causal relationships among green finance, green energy, green technology, and fintech indices. To ensure the reliability of our findings, we utilize daily data from reputable sources such as S&P Green Bond for green finance, S&P Global Clean Energy for green energy, Renewable Energy and Clean Technology for green technology, and S&P Kensho Future Payments for fintech indices. Following our objective, a Vector Autoregressive Regression (VAR) model is constructed first, followed by Granger causality and impulse response analysis. The causality results indicate bidirectional causal relationships between green finance and green energy and green technology, as well as one-way causal relationships from green finance to green technology and from green energy to green technology. Impulse response analysis shows that the green energy index is a significant shock transmitter to the green bond index. In contrast, the green technology index is a significant shock transmitter to the fintech index. The findings suggest that capital support for green finance is vital for promoting green energy and technology and supporting sustainable development.
Keywords: Fintech; Sustainable Development; Green Energy; Green Bond; Green Finance; Green Technology